Terrestrial herbivorous mammals in a mosaic of Cerrado, Atlantic Forest and land-use changes - Cyntia Cavalcante Santos (2019)
The Cerrado and Atlantic forest biodiversity hotspots have been experiencing rapid land-use changes in the last five decades resulting in habitat fragmentation, invasion of exotic species and biodiversity loss. Herbivore mammals are a key community to investigate the impacts of land-use changes on biodiversity, because they are directly influenced by the landscape structure. In a first step, we reviewed articles published between 2002 and 2018 about terrestrial mammals in contexts of land-use change in the Brazilian Cerrado. We found that negative responses of mammals to land-use changes were mainly associated with agriculture, livestock, roads and urban areas. Moreover, we identified big knowledge gaps, for example in the coverage of research areas or species. Secondly, we collected data on the community of herbivore mammals across gradients of land-use changes in the Bodoquena Plateau in Brazil between February 2016 and December 2017. We analyzed how and on which scale three landscape metrics (percentage of forest cover, patch density and edge density) affect the occurrence of four herbivore species (Dasyprocta azarae, Pecari tajacu, Mazama gouazoubira and Tapirus terrestris). We found differences in the scales at which the species responded to different landscape metrics. Finally, we modeled the occupancy of 23 herbivore mammals in the landscape of the Bodoquena Plateau. The pattern of occupancy as a function of forest cover percentage showed idiosyncratic responses per species to land-use changes. Therefore, we recommend different and complementary strategies including habitat restoration for conservation and management of herbivore mammals in the Bodoquena Plateau.